The determinants of financial development: institutions, openness and financial liberalisation. - Siong, Hook Law; Habibullah, Muzafar Shah (Wiley-Blackwell, 2009)
This paper provides new evidence that sheds light on the influence of institutional quality, trade openness and financial liberalisation on financial market development, using data from 27 economies (the G-7, Europe, East Asia and Latin America) during 1980-2001. The dynamic panel data analysis results demonstrate that real income per capita and institutional quality are statistically significant determinants of banking sector development and capital market development. The trade openness, however, is more prominent in promoting capital market development. In terms of financial liberalisation, the empirical results suggest that domestic financial sector reforms tend to promote banking sector development, whereas stock market liberalisation is potent in delivering stock market development. Nevertheless, the financial liberalisation programmes are more responsive in developed economies.